2022
DOI: 10.30802/aalas-jaalas-22-000058
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of 3 Buprenorphine Formulations for the Attenuation of Hypersensitivity after Plantar Incision in Immunodeficient NSG Mice

Abstract: Buprenorphine is perhaps the most prescribed analgesic for management of postoperative pain in mice. Although various buprenorphine formulations are effective in commonly used immunocompetent mouse strains, a knowledge gap exists regarding its efficacy in immunodeficient mice. Here we used a plantar incision to evaluate the efficacy of 3 buprenorphine formulations for attenuating postoperative mechanical and thermal hypersensitivity in the immunodeficient NSG mouse strain. We also characterized the pharmacokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 47 publications
0
0
0
Order By: Relevance
“…The duration of buprenorphine plasma levels greater than 1 ng/mL achieved by XR in the current study is similar to what has been previously reported, 14 although some previous studies report shorter 4 and longer 2,20,21 durations in mice. One study reported the duration of plasma levels greater than 1 ng/mL achieved by ER to be similar to our findings, 6 although several other studies report longer durations in mice.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The duration of buprenorphine plasma levels greater than 1 ng/mL achieved by XR in the current study is similar to what has been previously reported, 14 although some previous studies report shorter 4 and longer 2,20,21 durations in mice. One study reported the duration of plasma levels greater than 1 ng/mL achieved by ER to be similar to our findings, 6 although several other studies report longer durations in mice.…”
Section: Discussionsupporting
confidence: 91%
“…Because we found no difference between the drug groups and the saline group, we concluded that stress caused by daily anesthesia and blood collection was the likely cause of weight loss. Other studies have similarly found no difference in weight loss between XR and control 2,15,21 or XR and ER. 2,20 This finding suggests that potential drug-induced weight loss is not a critical factor in selecting buprenorphine formulations for mouse studies.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations